Pengetahuan Tes BTA Sebagai Prediktor Kepatuhan Pasien TB Menjalani Tes BTA - Wahyuni Wijayati; Eka Diah Kartiningrum (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Acid-fast bacilli (AFB) smear testing in TB patients plays an important role in diagnosis and is crucial to the success of TB control. Many factors influence compliance with AFB smear testing. The aim of this study was to analyze knowledge of AFB testing as a predictor of TB patient compliance with AFB testing at Bhayangkara HS Samsoeri Mertojoso Hospital in Surabaya. This study used a cross-sectional design from March to May 2025 with a sample of 85 TB patients selected by simple random sampling according to inclusion criteria. Data were collected using a questionnaire and then analyzed using logistic regression. The results of the study explain that the majority of respondents were of productive age, worked as private employees, lived <10 km from health facilities, had a high school education, and had good knowledge about BTA. Knowledge had a significant effect on compliance (P value = 0.000; R2 = 0.389 and PR = 9.249). Patients with good knowledge were 9.249 times more likely to comply with BTA examinations. Respondent compliance was high but not optimal in terms of the timeliness of examinations and retests after treatment. Patients' technical understanding of the function of sputum smear microscopy is still lacking, affecting their perception of compliance. These findings are consistent with the Health Belief Model and Social Support Theory, emphasizing that education, access, and family support integrated into patient support strategies can improve compliance. TB control efforts require contextual education, family involvement, and continuous monitoring to ensure that sputum smear microscopy is performed on time and completely.